The use of consortia for the internationalization of firms - Mota-Engil case study - Sousa, Maria João (2011)
Internationalization has been widely studied throughout the years. Broadly, it has been predicted as irrevocable and having increasing impact on firm-related strategy. Within entry modes, consortium, has not received as much attention as others. Hence, it seems important to understand how this specific entry mode allows the entrance of firms in the international markets. This study intends to answer the question of “how” to internationalize, anticipating the consortium as the most feasible way for construction firms to enter certain markets. The reasons that determine its choice concern the specificness of the projects, markets and of the firm. In the first part of the study, we review the existent literature on consortia as an entry mode and as a tool of internationalization used by construction firms. Through this review we build a framework that reveals the motivations that lead to this choice. In the second part, we present the case study of Mota-Engil, as a potential source of valuable information which may contribute to the understanding of the phenomenon under study. This case study corroborates the motivations found to create consortia. The paper closes with its contributions, limitations and suggestions for future researches.